2018
DOI: 10.1111/jpr.12195
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Spectroscopy Detects Prefrontal Activities During Rorschach Inkblot Method

Abstract: The present research investigated activities in the prefrontal cortex while performing the Rorschach inkblot method (RIM) using functional near-infrared spectroscopy. Participants who had no history of mental illness or external head injury were presented with three International RIM Cards (I, IV, V) for 30 s each and asked to identify what they looked like. In addition, a picture task was conducted, in which simple pictures were used as visual stimuli and participants were asked to say what they were. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…For example, greater electroencephalogram activations in frontal parietal cortices were observed as participants considered the meaning of a monochromatic inkblot as compared to a polygon shape; it is noteworthy that somatosensory cortical activation was also observed for both stimulus conditions [ 43 ]. In functional near-infrared spectroscopy studies, functional modulation near the parietal lobe [ 44 ] and bilateral activity in the rostral frontal cortex [ 45 ] were reported among college-aged adults observing inkblots. Therefore, it is plausible that perceptual and fluid cognitive functions of the splenium support the creation and communication of RIM responses as indexed by Sum6 and WSum6 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, greater electroencephalogram activations in frontal parietal cortices were observed as participants considered the meaning of a monochromatic inkblot as compared to a polygon shape; it is noteworthy that somatosensory cortical activation was also observed for both stimulus conditions [ 43 ]. In functional near-infrared spectroscopy studies, functional modulation near the parietal lobe [ 44 ] and bilateral activity in the rostral frontal cortex [ 45 ] were reported among college-aged adults observing inkblots. Therefore, it is plausible that perceptual and fluid cognitive functions of the splenium support the creation and communication of RIM responses as indexed by Sum6 and WSum6 .…”
Section: Discussionmentioning
confidence: 99%
“…Among healthy, young adults, greater EEG activations in frontal and parietal cortices were observed as participants considered the meaning of a monochromatic inkblot compared with a polygon shape; it is noteworthy that somatosensory cortical activation was also observed for both stimulus conditions (Luciani et al, 2014). Functional modulation (decrease in deoxygenation indexed by fNIRS) near the parietal lobe was reported in college-aged adults observing inkblots for 30 s versus neutral pictures (Aizawa et al, 2018). Another fNIRS study of adolescents found bilateral activity in the rostral frontal cortex during inkblot observation (Hiraishi et al, 2012), but the study was specifically designed to make comparisons with other picture-based personality assessments and did not report response variables.…”
Section: Neural Correlates Of Rorschach Responsesmentioning
confidence: 99%
“…Next, this special issue continues with nine original research articles and brief reports providing novel approaches in various fields of psychology. In the brief report by Aizawa et al (), the authors shed new light on the conventional clinical psychological test called the Rorschach inkblot method (RIM), and explore its neural basis in the function of the prefrontal cortex. They found task‐segment‐specific differential activation patterns in the prefrontal cortex during actual execution of RIM assessment using the International RIM Cards.…”
mentioning
confidence: 99%